Evolutionary medicine and bioastronautics: an innovative approach in addressing adverse mental health effects to astronauts during long term space missions - Saniotis, Arthur; Henneberg, Maciej; Mohammadi, Kazhaleh (Frontiers in Physiology, 2025)
Although evolutionary medicine has produced several novel insights for explaining prevalent health issues, it has yet to sufficiently address possible adverse mental health effects of humans during long-term space missions While evolutionary applications to medicine have increased over the past 20 years, there is scope for the integration of evolutionary applications in the new branch of space medicine called bioastronautics, which analyses the effects on human bodies when in outer space. Evolutionary principles may explain what kinds of space environments increase mental health risks to astronauts, both in the short and long term; secondly, evolutionary principles may provide a more informed understanding of the evolutionary mismatch between terrestrial and space environments in which astronauts exist. This information may assist in developing frameworks for improving mental health of astronauts and future space colonists. Consequently, this paper will focus on some of the major evolutionary mismatches currently confronting astronauts’ mental health, with an aim to improve medical knowledge. It will also provide possible therapeutic countermeasures based on evolutionary principles for reducing adverse mental effects on astronauts.